2018
DOI: 10.3389/fnana.2018.00085
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the Nose and Nasal Region of the Rat: Implications for Initiating the Mammalian Diving Response

Abstract: Most terrestrial animals demonstrate an autonomic reflex that facilitates survival during prolonged submersion under water. This diving response is characterized by bradycardia, apnea and selective increases in peripheral vascular resistance. Stimulation of the nose and nasal passages is thought to be primarily responsible for providing the sensory afferent signals initiating this protective reflex. Consequently, the primary objective of this research was to determine the central terminal projections of nerves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
1
12
0
1
Order By: Relevance
“…In guinea pigs, jugular vagal afferents evoke an apnea in anesthetized animals when stimulated and mediate coughing in response to inhaled noxious chemicals in conscious animals (Chou et al, 2008, 2018; Driessen et al, 2015, 2018). The apneic response, readily induced from the guinea pig larynx (Driessen et al, 2015, 2018), is perhaps consistent with the reported role of the paratrigeminal nucleus in the diving reflex whereby stimulation of trigeminal afferents in the nose promotes breath holding (Panneton et al, 2000; McCulloch et al, 2018). Indeed, the jugular vagal innervation to the larynx is particularly dense an either electrical stimulation or topically applied capsaicin evokes a profound withdrawal of respiratory drive.…”
Section: The Physiological Role Of the Paratrigeminal Nucleus In Vagasupporting
confidence: 82%
“…In guinea pigs, jugular vagal afferents evoke an apnea in anesthetized animals when stimulated and mediate coughing in response to inhaled noxious chemicals in conscious animals (Chou et al, 2008, 2018; Driessen et al, 2015, 2018). The apneic response, readily induced from the guinea pig larynx (Driessen et al, 2015, 2018), is perhaps consistent with the reported role of the paratrigeminal nucleus in the diving reflex whereby stimulation of trigeminal afferents in the nose promotes breath holding (Panneton et al, 2000; McCulloch et al, 2018). Indeed, the jugular vagal innervation to the larynx is particularly dense an either electrical stimulation or topically applied capsaicin evokes a profound withdrawal of respiratory drive.…”
Section: The Physiological Role Of the Paratrigeminal Nucleus In Vagasupporting
confidence: 82%
“…The novelty of our study is the observation that in these freezing water conditions, after a quick increase at the beginning of the dives, parasympathetic (PNS) activity actually decreased for HRV measures at 5-0 min. The first PNS response (M1) could be explained with a strong diving reflex at the beginning of the dives (Konishi et al, 2016;Schaller et al, 2017;Vega, 2017;McCulloch et al, 2018;Schlader et al, 2018). The next measure (M2) may suggest that, in humans, the diving reflex-induced PNS response actually decreased after a while.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that pulmonary veins are a functional reservoir of blood for the cardiovascular system. Sympathetic vasoconstriction of the pulmonary veins can be essential for mobilizing a given volume of blood under general stress conditions of the cardiovascular system (Morman and Heller, 2000).…”
Section: Discussionmentioning
confidence: 99%